Growth Performance of Calves of Nattukuttai Cattle under Different Feeding Regimes - Sundharesan, S.R.; A.Yasotha; M.Murugan; K.Loganathasamy (The Indian Veterinary Journal, 2026)
A study to assess the growth performance of Nattukuttai calves under different feeding regimes in an organized farm for a period of 5 months. 18 calves of age 3 to 4 months, divided into 3 groups (T1, T2 and T3). The T1 calves allowed for grazing only, T2 calves fed with only roughages and T3 calves fed concentrates along with roughages based on total dry matter requirement. Parameters such as fortnightly body weight, body weight gain, average daily gain, dry matter intake, feed conversion ratio, body measurements and body condition score revealed no significant difference among the groups. However numerically higher body weight, BWG, ADG and BCS were observed in T3 group followed by T2 and T1. This study gives the baseline data on the growth parameters of Nattukuttai cattle calves.